2022
DOI: 10.3389/fpsyt.2022.1063489
|View full text |Cite
|
Sign up to set email alerts
|

Potential mechanisms underlying the therapeutic roles of sinisan formula in depression: Based on network pharmacology and molecular docking study

Abstract: BackgroundThe incidence of depression has been increasing globally, which has brought a serious burden to society. Sinisan Formula (SNSF), a well-known formula of traditional Chinese medicine (TCM), has been found to demonstrate an antidepressant effect. However, the therapeutic mechanism of this formula remains unclear. Thus, the present study aimed to explore the mechanism of SNSF in depression through network pharmacology combined with molecular docking methods.Materials and methodsBioactive compounds, pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Studies have shown that the content of DFV in the same lifetime of PR is lower than β-sitosterol but higher than other active compounds [ 70 ]. β-sitosterol has been proven to exist as a potential active ingredient in antidepressant formulations in multiple network pharmacology studies [ 71 , 72 ]. Therefore, this study selected DFV with a smaller molecular weight (MW: 256.27) as the compound to be validated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the content of DFV in the same lifetime of PR is lower than β-sitosterol but higher than other active compounds [ 70 ]. β-sitosterol has been proven to exist as a potential active ingredient in antidepressant formulations in multiple network pharmacology studies [ 71 , 72 ]. Therefore, this study selected DFV with a smaller molecular weight (MW: 256.27) as the compound to be validated.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [ 57 ] conducted research using molecular docking and network pharmacology to investigate the mechanism of Sinisan Formula (SNSF) in treating depression. SNSF is a widely recognized TCM formula that comprises four herbs: Licorice (Gancao), Aurantii Fructus Immaturus (Zhishi), Paeoniae Radix Alba (Shaoyao), and Bupleurum chinense (Chaihu).…”
Section: Overview Of Tcmmentioning
confidence: 99%
“…Over the last decade, there has been a rapid increase in CADD-based studies of depression, including docking studies of ligands for serotonin reuptake [171,172], MAO A and MAO B [173,174], dual action on MAO-B/AChE [175], glycogen synthase kinase [176], sodium hNaV1.2 or hNaV1.7 channels [177], serotonin receptors (5HT1A, 5-HT2A, 5-HT2C and 5-HT4) [171,[178][179][180][181], adenosine A1/A2A receptors [182], T-type calcium channels [183], tryptophan 2,3-dioxygenase [184] and sigma receptor [185]. Similarly, application of docking in psychoses involved ligands for serotonin 5HT2 and dopamine D2 receptors [186], α4β2 and α7 nicotinic acetylcholine receptors [187,188], phosphodiesterase 10A [189], MAO A and B [190], a syntaxin-binding protein (STXBP1) [191], NMDA type subunit 1 (GRIN1) [192], fatty acid binding protein 7 (FABP7) [193,194], metabotropic glutamate mGluR5 receptor [195], ionotropic GABA-A receptor [196], glycine transporter type 1 (GlyT1) [197] and kynurenine aminotransferase II (KATII) [198].…”
Section: In Silico-driven Search For Novel Therapeutic Agentsmentioning
confidence: 99%
“…In general, network pharmacology utilizes the systems biology methods to analyze biological networks (e.g., metabolic or signaling pathways, protein-protein interactions) in order to infer drug actions and interactions with various targets [199]. Multiple recent studies have revealed drug targets of phytocomponents from extracts with antidepressant effects [193,194,[200][201][202], and a similar approach has been used to search for drug targets related to the treatment of schizophrenia by known schizophrenia drugs [203]. Some studies also combine docking with (Q)SAR methods, e.g., identifying monoamine neurotransmitters reuptake inhibitors as antidepressants [204] or a selective positive allosteric modulation of α1containing GABA-A receptors [196].…”
Section: In Silico-driven Search For Novel Therapeutic Agentsmentioning
confidence: 99%